The Effect of Student's Family Environment and Learning Interests on Learning Outcomes in The Computer Programming Subject at Vocational High School's Distance Learning Context - Ervyn Vania Riswara; Admaja Dwi Herlambang; Tri Afirianto (Journal of Information Technology and Computer Science, 2022)
During the Covid-19 pandemic, the learning process was carried out remotely in each home using a learning platform that had been determined by the school. In the current situation to support the quality of the student learning process at home, a good family environment is needed so that students get good learning outcomes. Distance learning can also affect student interest in learning, due to the lack of interaction and lack of socialization between teachers and students, and many other factors affect student interest in learning. So the researcher wants to calculate how the influence of the family environment and student interest in learning during the pandemic period on the learning outcomes of class X RPL students of SMK Negeri 9 Malang in Basic Programming subjects. This study uses quantitative research along with correlational methods with a sample of 101 students of class X RPL SMK Negeri 9 Malang. The research data obtained comes from the results of distributed questionnaires and documentation. The data analysis used is the regression test, correlation test, T-test and F test using SPSS 25 software. From the research that has been done, the results are (1) there is an influence by the family environment on student learning outcomes with a significance value of 0.047 < 0.05 , (2) interest in learning affects learning outcomes with a significance value obtained at 0.001 < 0.05, (3) family environment and interest in learning simultaneously affect student learning outcomes with a significance value of 0.000 < 0.05.